2004
DOI: 10.1094/pdis.2004.88.10.1164a
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Pear blister canker viroid, Peach latent mosaic viroid, and Hop stunt viroid Infecting Fruit Trees in Tunisia

Abstract: Viroids of fruit trees are plant pathogens distributed worldwide and can cause severe losses and economic damage to crops. A survey of fruit trees was carried out in 17 orchards in the northern and Sahel regions of Tunisia. Samples were collected in field trees of peach (Prunus persica L), pear (Pyrus communis L), and almond (Prunus dulcis Mill.) that showed symptoms potentially caused by viroids (leaf mosaic in peach, blister canker in pear, and necrotic leaves in almond). The investigation was conducted duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…PLMVd is known to infect peach (Prunus persica) in Europe, Asia, Africa, and both North and South America (Hadidi et al, 1997;Pelchat et al, 2000;Fekih Hassen et al, 2004). It has also been detected occasionally in apricot (Prunus armeniaca), plum (Prunus domestica), sweet cherry (Prunus avium), cultivated pear (Pyrus communis), wild pear (Pyrus amygdaliformis), mume (Prunus mume), and almond (Prunus amygdalus) (Faggioli et al, 1997;Hadidi et al, 1997;Kyriakopoulou et al, 2001;Fekih Hassen et al, 2004.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PLMVd is known to infect peach (Prunus persica) in Europe, Asia, Africa, and both North and South America (Hadidi et al, 1997;Pelchat et al, 2000;Fekih Hassen et al, 2004). It has also been detected occasionally in apricot (Prunus armeniaca), plum (Prunus domestica), sweet cherry (Prunus avium), cultivated pear (Pyrus communis), wild pear (Pyrus amygdaliformis), mume (Prunus mume), and almond (Prunus amygdalus) (Faggioli et al, 1997;Hadidi et al, 1997;Kyriakopoulou et al, 2001;Fekih Hassen et al, 2004.…”
Section: Introductionmentioning
confidence: 99%
“…PLMVd is known to infect peach (Prunus persica) in Europe, Asia, Africa, and both North and South America (Hadidi et al, 1997;Pelchat et al, 2000;Fekih Hassen et al, 2004). It has also been detected occasionally in apricot (Prunus armeniaca), plum (Prunus domestica), sweet cherry (Prunus avium), cultivated pear (Pyrus communis), wild pear (Pyrus amygdaliformis), mume (Prunus mume), and almond (Prunus amygdalus) (Faggioli et al, 1997;Hadidi et al, 1997;Kyriakopoulou et al, 2001;Fekih Hassen et al, 2004. Molecular variants isolated from European and North American sources have 335 to 351 nt and showed high naturally occurring polymorphism (Hernandez and Flores, 1992;Shamloul et al, 1995;Ambros et al, 1998;Pelchat et al, 2000;Malfitano et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings reveal for the first time natural mixed infections of apple and wild apple with ASSVd, PBCVd and HSVd, of quince with ASSVd and PBCVd and of wild apple and sweet cherry with ASSVd and HSVd. Mixed viroid infections of ASSVd, PBCVd and Peach latent mosaic viroid (PLMVd) in pear and wild pear (Kyriakopoulou et al, 2001), of PLMVd and HSVd in peach (Prunus persica) (Hassan et al, 2004;Tessitori et al, 2002) and of PBCVd, PLMVd and HSVd in pear (Fekih-Hassen et al, 2004) have been reported previously. The presence of natural viroid infections in wild species away from human influence in Greece suggests that ASSVd, PBCVd and PLMVd originated in wild hosts and are probably native to Greece (Kyriakopoulou et al, 2001); our data for ASSVd, PBCVd and HSVd support this hypothesis (Kaponi 2009).…”
mentioning
confidence: 87%
“…In Spain, while the native cultivars were not infected, the percentage of imported and infected varieties reached 85% (Badenes and Llacer, 1998). PLMVd has been detected in other species of fruit trees, such as apricot ( Prunus armeniaca ), plum ( Prunus domestica ), sweet cherry ( Prunus avium ), cultivated pear ( Pyrus communis ) and wild pear ( Pyrus amygdaliformis ) from European countries (Faggioli et al., 1997; Hadidi et al., 1997; Kyriakopoulou et al., 2001) and recently, pear and almond ( Prunus amygdalus ) from Tunisia (Fekih Hassen et al., 2004, 2005). The economic importance of PLMVd derives from the fruit alterations, reduced tree longevity and increased susceptibility to other biotic or abiotic stress (Flores et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Peach culture has an economic importance in Tunisia as it occupied more than 22 000 hectares producing approximately 108 000 tons in 2005. A preliminary survey revealed that the PLMVd was present in Tunisian orchards and it represents one of the most important threats for the peach production (Fekih Hassen et al., 2004). Several questions rose from this preliminary study: what is the incidence of PLMVd in different Tunisian regions?…”
Section: Introductionmentioning
confidence: 99%